EVALUATION OF GURU PENGGERAK PERFORMANCE - Kadir, Aswin Anwar Abdul; Samsudin; Subandi, Oman U. (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Frequent changes in educational goals and policies in Indonesia have significantly impacted on teachers. Thus, the government has initiated a development program called the Guru Penggerak Program to prepare teachers for implementing the Merdeka Curriculum. This study aims to evaluate the performance of teachers who have participated in the Guru Penggerak Program. The method used in this research is descriptive qualitative, employing questionnaire and interview techniques. The data in this study consists of 36 Guru Penggerak teachers, 72 colleagues, 72 students, and 20 school principals from various educational levels, including elementary, junior high, and senior high/vocational schools. Besides identifying teacher performance, the results are expected to explain the impact of the Guru Penggerak Program on the school community as reflected in the performance of the Guru Penggerak teachers. The research findings indicate an improvement in the quality of Guru Penggerak teachers in conducting educational activities, both in teaching and in personal and social development. Guru Penggerak teachers can collaborate with students in educational activities and are becoming actively involved in leading learning. Overall, the Guru Penggerak Program followed by teachers in Sorong City has provided new insights for teachers and positive impacts on colleagues, students, and school leaders.